2022
DOI: 10.3390/v14061213
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Immunity among Five Medically Important Mosquito-Borne Flaviviruses Related to Human Diseases

Abstract: Flaviviruses cause a spectrum of potentially severe diseases. Most flaviviruses are transmitted by mosquitoes or ticks and are widely distributed all over the world. Among them, several mosquito-borne flaviviruses are co-epidemic, and the similarity of their antigenicity creates abundant cross-reactive immune responses which complicate their prevention and control. At present, only effective vaccines against yellow fever and Japanese encephalitis have been used clinically, while the optimal vaccines against ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…In South America, Central America, and the Caribbean, different geographic regions have multiple endemic mosquito-borne flaviviruses in co-circulation [ 75 , 76 , 77 ]. Twenty-nine (78.3%) of the 37 studies included in our meta-analysis investigated the antibody ratios against multiple arbovirus antigens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In South America, Central America, and the Caribbean, different geographic regions have multiple endemic mosquito-borne flaviviruses in co-circulation [ 75 , 76 , 77 ]. Twenty-nine (78.3%) of the 37 studies included in our meta-analysis investigated the antibody ratios against multiple arbovirus antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Flavivirus species have been linked to sporadic cases of human infection, including Bussuquara (BUSV), Cacipacore (CPCV), and ILHV [ 78 , 79 ]. All these viral pathogens may cause undifferentiated febrile illness in humans, and laboratory diagnosis is difficult due to the substantial cross-reactivity of antibodies [ 75 ]. Additionally, as occurs for ILHV, BUSV, CPCV, and other native flaviviruses are neglected, with misdiagnosis of cases compared to other medical arboviruses associated with outbreaks or epidemics that attract the most public attention, such as DENV, ZIKV, and YFV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koblischke et al [ 210 ] reported peptide regions that form the immune-dominant WNV E epitopes, and one such region (E149) is unique and absent in DENV and ZIKV and lies on a structurally divergent region in WNV. Multiple research findings from mouse experiments and human studies revealed the essential role of cellular immunity and neutralizing antibodies in cross-protection between primary JEV or WNV exposure and secondary DENV and ZIKV infections [ 212 ]. The sequence of infection is known to influence disease outcomes; additionally, immune-dominant mechanisms of protection for each dyad of viral infections can be distinct and essential to elucidate if these outcomes are to inform therapeutics.…”
Section: Je Serocomplex Flavivirus Immune Responsementioning
confidence: 99%
“…For instance, in the sequential JEV-ZIKV infection, unlike the JEV-JEV infection, JEV vaccination-induced CD8 T cell immunity was found to be essential for conferring cross-protection in mouse models compared to passive transfer of serum [ 213 , 214 ]. Alternatively, cross-protective outcomes in JEV-DENV1 infection in mouse models required the cooperative effects of humoral and T cell responses, whereas in human infections, secondary DENV following anti-JEV immunity resulted in manifestation of increased viral symptoms [ 206 , 212 , 215 ].…”
Section: Je Serocomplex Flavivirus Immune Responsementioning
confidence: 99%